1988
DOI: 10.1161/01.cir.78.3.598
|View full text |Cite
|
Sign up to set email alerts
|

New catheter technique for recording left free-wall accessory atrioventricular pathway activation. Identification of pathway fiber orientation.

Abstract: The ability to record accessory atrioventricular (AV) pathway activation consistently may be uniquely beneficial in improving pathway localization, identifying anatomic relations, and providing insight into unusual conduction properties. For the purpose of recording left AV accessory pathway activation, an electrode catheter was specially designed for use in the coronary sinus. The orthogonal catheter has three sets of four electrodes spaced evenly around the circumference. Electrograms were recorded at low ga… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
38
0
4

Year Published

1990
1990
2019
2019

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 126 publications
(42 citation statements)
references
References 33 publications
(4 reference statements)
0
38
0
4
Order By: Relevance
“…Ventricular activation recorded from the MCV, PCV, or CS diverticulum preceded endocardial ventricular activation (Figure 2). A highfrequency potential similar to an antegrade accessory pathway activation potential, 15 presumably generated by an extension of the CS myocardial coat (Figures 1 and 3) was recorded from the MCV, PCV, or neck of a CS diverticulum before the earliest far-field ventricular potential, and the antegrade CSE potential was dissociated from local atrial and ventricular activation by the use of ventricular extrastimuli ( Figure 4). 15 …”
Section: During Antegrade Accessory Pathway Conductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Ventricular activation recorded from the MCV, PCV, or CS diverticulum preceded endocardial ventricular activation (Figure 2). A highfrequency potential similar to an antegrade accessory pathway activation potential, 15 presumably generated by an extension of the CS myocardial coat (Figures 1 and 3) was recorded from the MCV, PCV, or neck of a CS diverticulum before the earliest far-field ventricular potential, and the antegrade CSE potential was dissociated from local atrial and ventricular activation by the use of ventricular extrastimuli ( Figure 4). 15 …”
Section: During Antegrade Accessory Pathway Conductionmentioning
confidence: 99%
“…The earliest high-frequency potential (similar to a retrograde AP potential) 15 was recorded from the MCV, PCV, or neck of a CS diverticulum, and was presumably generated by an extension of the CS myocardial coat (CSE in Figure 5). The CSE potential was followed by activation of the CS myocardial coat, with the earliest CS myocardial coat potential recorded near the orifice of the vein ( Figure 5A, first complex, CS 1 in electrograms MCV-Bip 3-4 and CS 9 ).…”
Section: During Retrograde Accessory Pathway Conductionmentioning
confidence: 99%
“…24 The catheter was inserted percutaneously into the left subclavian vein, right internal jugular vein, or the left antecubital vein and was advanced into the coronary sinus and positioned as far anteriorly as possible in the great cardiac vein. Close bipolar electrograms with the recording dipole oriented perpendicular to the axis of the catheter were obtained by recording between adjacent electrodes within a circumferential group of electrodes.…”
Section: Mapping the Mitral Anulusmentioning
confidence: 99%
“…Of the 33 left free-wall (24) and posteroseptal (9) accessory pathways that never exhibited antegrade conduction, the site of permanent antegrade block was at or near the ventricular interface in 29 ( Figure 6). Pacing the accessory pathway directly in one patient still failed to produce ventricular preexcitation ( Figure 7).…”
Section: Concealed Accessory Pathwaysmentioning
confidence: 99%
“…For all subjects, the CS electrode catheter could be inserted into the peripheral anterior region of the CS lumen. According to the EPS conducted by Jackman, et al, 13) the CS lumen in the left anterior oblique (60°) view was divided into six equal segments alphabetically, termed A to F, from the distal CS terminal as shown in Figure 1A. All atrial components of the unipolar CS electrogram showed the fundamental biphasic configuration composed of initial positive and secondary negative parts.…”
Section: Patientsmentioning
confidence: 99%